STUDYING THE DYNAMICS OF VOCAL PERFORMANCE - Boratov Shukurjon Imomaliyevich (Journals Park Publishing, 2024)
Vocal performance is a complex interaction of physiological, psychological and artistic factors that contribute to the creation of engaging musical experiences. This scientific article explores the subtleties of vocal performance, examining the role of technique, expression, stage presence and audience participation in shaping the quality and impact of vocal presentations. By conducting a systematic review following the IMRAD framework, this study aims to provide insight into the multifaceted nature of vocal performance and its implications for performers and audiences.
Keywords: Vocal performance, technique, expression, stage presence, audience engagement.